1979
DOI: 10.1111/j.1476-5381.1979.tb13663.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐HYDROXYTRYPTAMINE UPTAKE INHIBITORS BLOCK para‐METHOXYAMPHETAMINE‐INDUCED 5‐HT RELEASE

Abstract: I Activation of myoclonic twitch activity (MTA) of suprahyoideal muscle after p-methoxyamphetamine (PMA) administration in rats anaesthetized with urethane has previously been reported to be due to brain 5-hydroxytryptamine (5-HT) release. Increased MTA caused by PMA was blocked by chlorimipramine (0.1 to 1 mg/kg) and fluoxetine (0.3 to 3 mg/kg) but not by desipramine (3 mg/kg).2 The 5-hydroxytryptophan-induced increase of MTA of suprahyoideal muscle in rats pretreated with pargyline was not blocked by chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The range of agents examined encompasses the metabolic precursors of serotonin, L-tryptophan and L-5-hydroxytryptophan [1,3,6,10,17]; releasers such as fenfluramine [37], chloroamphetamine [ 12], and methoxyamphetamine [9]; uptake inhibitors (e.g., fluoxetine [17]), chlorimipramine [10]; and receptor agonists, such as 2,5-methoxyamphetamine [38], tryptamine [1], 5-methoxydimethyltryptamine [ 1,17], MK212 [ 1 ], and quipazine [1]. The latter two compounds are remarkable in that their effects show a dose-dependence over a 100-fold range, with peak swallowing rates (~ 100/min) approaching the maximum frequency obtainable with electrical stimulation of the superior laryngeal nerve.…”
Section: Serotoninergic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of agents examined encompasses the metabolic precursors of serotonin, L-tryptophan and L-5-hydroxytryptophan [1,3,6,10,17]; releasers such as fenfluramine [37], chloroamphetamine [ 12], and methoxyamphetamine [9]; uptake inhibitors (e.g., fluoxetine [17]), chlorimipramine [10]; and receptor agonists, such as 2,5-methoxyamphetamine [38], tryptamine [1], 5-methoxydimethyltryptamine [ 1,17], MK212 [ 1 ], and quipazine [1]. The latter two compounds are remarkable in that their effects show a dose-dependence over a 100-fold range, with peak swallowing rates (~ 100/min) approaching the maximum frequency obtainable with electrical stimulation of the superior laryngeal nerve.…”
Section: Serotoninergic Mechanismsmentioning
confidence: 99%
“…In predictable fashion, agents capable of releasing catecholamines from neuronal storage pools stimulate deglutition, as exemplified by (+)-amphetamine [3,6,12,26] and meta-methoxyamphetamine [9][10][11]. Catecholaminergic stimulation was initially attributed solely to an action at dopamine receptors [3], on account of the excitant action of the direct dopmine receptor agonist, apomorphine, and the lack of action of D,L-threo-3,4-dihydroxyphenylserine, which can undergo direct conversion to noradrenaline [30].…”
Section: Catecholaminergic Mechanismsmentioning
confidence: 99%
“…5 Early studies with PMA have revealed that PMA administration results in myoclonic twitch activity and induces release of 5-HT in the central nervous system. 6 It has also been demonstrated that PMA induces hyperthermia and that this hyperthermia is primarily a result of influence on the 5-HT system. 7 In vitro studies have revealed that PMA is more than 20 times as potent as (+)-amphetamine as an inhibitor of 5-HT oxidation by monoamine oxidase in mouse brain with a K I value of 0.22 µM.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies with PMA have revealed that PMA administration results in myoclonic twitch activity and induces release of 5‐HT in the central nervous system 6. It has also been demonstrated that PMA induces hyperthermia and that this hyperthermia is primarily a result of influence on the 5‐HT system 7.…”
Section: Introductionmentioning
confidence: 99%